Impact of R&D on the Innovation of Products and Processes in Latin Countries - Rodrigo Esteban Ortiz Henriquez; Fernando A. Crespo; Cristian Geldes; Tiago Alves Ferreira; Mauricio Castillo-Vergara (Axioms, 2023)
According to the literature on innovation, several vital factors or determinants favor innovation in companies. In the case of R&D, significant advances have been made in the last two decades, which have enriched our understanding of its impact on various innovation outcomes. However, due to a lack of data availability, its study is difficult to address in emerging markets. This is why, using microdata from 5588 firms, we investigate the relationship between R&D investment and the impact on product and process innovations in different Latin American countries. We contribute to the literature by employing a machine learning methodology and comparing its results to a traditional innovation model. Our findings demonstrate the behavior of both product and process innovation methods.